Psychosocial Determinants of Marital Satisfaction Among Gynecologic Cancer Survivors in Malaysia - Hatta, Sidi; Woon, Luke Sy-Cherng; Nik Sumayyah, Nik Mohd Nor; Mohamad Nasir, Shafiee (Frontiers in Psychiatry, 2021)
Introduction: Marital issues among gynecologic cancer survivors are common but complex. This study aimed to investigate the relationship between sociodemographic and clinical factors, including sexual dysfunction and marital satisfaction among Malaysian gynecologic cancer survivors. Methods: A cross-sectional survey of married women with gynecologic cancers was conducted at a Malaysian university hospital. Sociodemographic and clinical data were gathered. Sexual dysfunction was measured using the Malay Version Female Sexual Function Index (MVFSFI), while marital satisfaction was evaluated with the Malay Version Golombok Rust Inventory for Marital Satisfaction (MVGRIMS). Results: A total of 116 patients participated in this study. The median age was 59.0 years (Interquartile range, IQR: 49.0-67.0 years); the median duration of marriage was 32 years (IQR: 20.0-40.8 years). 80.2% had a secondary and lower level of education. 37.9% of study subjects (n=44) reported poor and below levels of marital satisfaction, which was equivalent to MVGRIMS transformed scores of >5. The median FSFI total score was 49.9 (IQR: 2.0-63.0). 37.9% of the patients reported poor-and-below levels of marital satisfaction (MVGRIMS transformed score >5). MVGRIMS transformed score correlated significantly with all MVFSFI sub-scores. In logistic regression, lower educational levels were associated with poor marital satisfaction (primary, [adjusted Odds Ratio] aOR=12.67, 95%CI: 1.40-114.87; secondary: aOR=11.52, 95%CI: 1.39-95.72), while higher MVFSFI total score reduced the likelihood of poor marital satisfaction (aOR=0.979, 95%CI: 0.964-0.994). Conclusion: Both sexual dysfunction and low education level may affect marital satisfaction among gynecologic cancer survivors. Targeted efforts focusing on sex education for patients may help to improve marital satisfaction.